Forensics: Food Authentication Using MtDNA - Chandrika Murugaiah; Hassanain Al-Talib; Son Radu (Symbiosis, 2015)
There is a clear trend in the food international market towards labelling products with information about their composition and quality. Due to the increase in international trade in seafood and seafood products, authentication has become a necessity. There is a need for suitable methods of identification to ensure compliance with the labelling regulations and thereby to prevent the substitution of fish species.